Special issue: 2016 International Conference on Information Technology in Medicine and Education (ITME2016). (18th July 2019) - Chen, Jinjun
Summary: This special issue contains selected high‐quality papers from the 2016 International Conference on Information Technology in Medicine and Education (ITME2016), which was held on December 23‐25, 2016 in Fuzhou, China. The ITME conference series aims to provide an international forum for the presentation and discussion of research and development trends regarding information technology in medicine and education. The ITME2016 attracted many international attendants, allowing deep discussion and the exchange of ideas and results related to ongoing research among attendants. This special issue contains nine papers based on those that were presented at ITME2016. Among these are those by Liu et al, Lin et al, Zhang et al, Lin et al, Zhou et al, Cai et al, Li et al, Zheng et al, and Dai et al, 2018. Research problems in these papers have been analyzed systematically, and for specific approaches or models, evaluation has been performed to demonstrate their feasibility and advantages. The papers were selected on this basis and also peer reviewed thoroughly. The nine papers reflect a vision of the area in state‐of‐art fashion.